Education: The Use of Vitamins and Drugs for Covid 19 During the Pandemic in Mangkurakyat Village, Cilawu Garut District - Retty Handayani; Anggi Riswan Safarinoer; Muhamad Abdilah; Neng Elsa; Nida Amalia; Nurfajriyanti Nurfajriyanti; Raja Andri Hidayat (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The increasing number of positive cases of covid 19 in various regions and the high death rate have led to a lot of recommendations to increase endurance in various media, this has led to "panic buying" among the public to buy vitamins and drugs for covid 19 at pharmacies without a prescription. This educational activity is carried out through several stages starting from targeting, preparation, implementation of education and evaluation. Education was given to cadres in Mangkurakyat Village, Cilawu District, Garut Regency. This activity was carried out in the form of lectures and questions and answers which took place in the village hall with limited participants and following the health protocol according to the provisions. The results of the evaluation (pretest-posttest) showed a significant change where before the posteat only 6.6% of participants knew about the use of vitamins and drugs for COVID-19 after education to 98.6%.